Performance assessment of steel–concrete composite bridges with subsurface deck deterioration. (June 2015) - Gheitasi, Amir; Harris, Devin K.
Abstract: In-service composite steel girder bridges typically experience a variety of deterioration mechanisms during their service lives, ranging from cracking, spalls, and delaminations in the reinforced concrete deck to corrosion in the steel girders. To date, several inspection techniques and novel technologies have been widely implemented to identify and measure different sources of defects associated with bridge systems, especially within the concrete deck. Despite successful implementation of these evaluation methodologies, what transportation agencies still lack is a fundamental understanding of the system-level behavior and the potential impact of the identified deterioration conditions on the overall performance of these bridges. In this paper, the impact of corrosion-induced subsurface deck delamination on the overall behavior and performance of steel–concrete composite bridges is investigated using finite element simulation and analysis. The accuracy and validity of the modeling approaches were assessed through a comparison to experimental data available in literature. A sensitivity study was performed to investigate the influence of deck deterioration on the system-level performance, load distribution behavior, and failure characteristics of two representative composite steel girder bridges. One of the selected structures is a full-scale laboratory bridge model, while the other one is an actual in-service structure with geometrical characteristics that represents typical features of steel girder bridges in Virginia. The selected damage scenarios included variations in different geometrical characteristics such as location and depth of damage, as well as degradation in material properties at the corresponding damaged areas. In addition to the bridge system behavior, the impact of rebar corrosion and subsurface delamination on the behavior of individual deck systems was investigated; while its implication on the current design methodologies for reinforced concrete decks was evaluated. Results from this investigation demonstrate that the deck deterioration has minimal impact on the overall system behavior and the path to failure of the selected structures, but may impact the failure characteristics in the form of reductions in the ultimate load-carrying capacity and system ductility. Graphical abstract: